Association of Helicobacter Pylori and Portal Hypertensive Gastropathy in Patients with Cirrhosis of Liver (Bangladesh Medical Journal, 2022)
Portal hypertensive gastropathy (PHG) is a common endoscopic finding in patients of cirrhosis of liver. The cause and pathogenesis of PHG in cirrhotic patients is poorly understood. Some studies showed, association of Helicobacter pylori (H. Pylori) with portal hypertensive gastropathy in cirrhosis of liver, but the evidence is not robust. The aim of this study was to assess the association of H. pylori infection and PHG in patients with cirrhosis of liver. This case control study was conducted in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from April 2016 to August 2018. A total of 230 patients with cirrhosis of liver were included in this study. There were 115 cirrhotic patients with PHG as cases and 115 cirrhotic patients without PHG as controls.  Upper gastrointestinal Endoscopy and 13C Urea Breath Test (UBT) was done in both cases and controls. In this study, out of 230 cases, 147 (63.91%) found to have H. pylori infection. Among cirrhotic patients with PHG case, 77 (66.95%) was positive in UBT. Out of these 77 UBT positive cases, 55 had mild PHG whereas 22 cases had severe form of PHG. Among 38 cases of cirrhosis with PHG who had negative UBT, 23 had mild PHG and 15 cases had severe form of PHG. The risk of positive urea breath test was not statistically significant in cirrhotic patients with PHG in comparison with cirrhotic patients without PHG (P=0.337, OR 1.303, 95% CI 0.759-2.235). In this study, statistically significant association was not found between H. Pylori and PHG in cirrhotic patients.Bangladesh Med J. 2021 May; 50(2) : 21-27